Answer:
x = (-1 + √(26)i)/9
x = (-1 - √(26)i)/9
Step-by-step explanation:
If we have an equation of the form ax² + bx + c = 0, we can solve it using the quadratic equation
![x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/rxvf73usjbbwyik14knxdemoz21vfz2ufc.png)
In this case, the given equation is
9x² + 2x = -3
This can be rewritten as
9x² + 2x + 3 = -3 + 3
9x² + 2x + 3 = 0
So, a = 9, b = 2 and c = 3. Therefore, the solutions using the quadratic equation are
![\begin{gathered} x=\frac{-2\pm\sqrt[]{2^2-4(9)(3)}}{2(9)} \\ x=\frac{-2\pm\sqrt[]{-104}_{}}{18} \\ x=\frac{-2\pm\sqrt[]{104}i}{18} \\ x=\frac{-2\pm2\sqrt[]{26}i}{18} \\ \text{Then} \\ x=\frac{-2+2\sqrt[]{26}i}{18}=\frac{-1+\sqrt[]{26}i}{9} \\ or \\ x=\frac{-2-2\sqrt[]{26}i}{18}=\frac{-1-\sqrt[]{26}i}{9} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zbrqppx17g5gnaovxduamgzk76v8e33ln2.png)
therefore, the solutions are
x = (-1 + √(26)i)/9
x = (-1 - √(26)i)/9